Design, Synthesis, Antimicrobial Properties, and Molecular Docking of Novel Furan-Derived Chalcones and Their 3,5-Diaryl-∆2-pyrazoline Derivatives - Inas S. Mahdi; Ahmed Mutanabbi Abdula; Abdulkadir M. Noori Jassim; Younis Baqi (MDPI AG, 2023)
The present work focuses on the synthesis and preliminary structure activity relationships (SARs) of furan-derived chalcones and their corresponding ∆2-pyrazoline derivatives as antimicrobial agents. Eight novel chalcone derivatives and eight ∆2-pyrazoline compounds were synthesized in moderate to good isolated yields. The target compounds were evaluated as antimicrobial agents against two Gram-positive (Staphylococcus aureus and Staphylococcus epidermidis), two Gram-negative (Escherichia coli and Klebsiella pneumoniae), and fungi (Candida albicans) species. Based on the SARs, chalcones 2a and 2h showed inhibition activity on all tested microbial species, while ∆2-pyrazoline 3d was found to be selective for some microbial species. The most potent compounds (2a, 2h, and 3d) were docked into glucosamine-6-phosphate synthase (GlcN-6-P), the molecular target enzyme for antimicrobial agents, utilizing the Autodock 4.2 program, in order to study their virtual affinity and binding mode with the target enzyme. The selected potent compounds were found to bind to the active site of the enzyme probably in a similar way to that of the substrate as suggested by the docking study. In summary, the newly developed furan-derived chalcones and their ∆2-pyrazoline derivatives could serve as potent leads toward the development of novel antimicrobial agents.